Species traits elucidate crop pest response to landscape composition: a global analysis. Issue 1937 (28th October 2020) - Tamburini, Giovanni; Santoiemma, Giacomo; E. O'Rourke, Megan; Bommarco, Riccardo; Chaplin-Kramer, Rebecca; Dainese, Matteo; Karp, Daniel S.; Kim, Tania N.; Martin, Emily A.; Petersen, Matt; Marini, Lorenzo
Abstract : Recent synthesis studies have shown inconsistent responses of crop pests to landscape composition, imposing a fundamental limit to our capacity to design sustainable crop protection strategies to reduce yield losses caused by insect pests. Using a global dataset composed of 5242 observations encompassing 48 agricultural pest species and 26 crop species, we tested the role of pest traits (exotic status, host breadth and habitat breadth) and environmental context (crop type, range in landscape gradient and climate) in modifying the pest response to increasing semi-natural habitats in the surrounding landscape. For natives, increasing semi-natural habitats decreased the abundance of pests that exploit only crop habitats or that are highly polyphagous. On the contrary, populations of exotic pests increased with an increasing cover of semi-natural habitats. These effects might be related to changes in host plants and other resources across the landscapes and/or to modified top-down control by natural enemies. The range of the landscape gradient explored and climate did not affect pests, while crop type modified the response of pests to landscape composition. Although species traits and environmental context helped in explaining some of the variability in pest response to landscape composition, the observed large interspecific differences suggest that a portfolio of strategies must be considered and implemented for the effective control of rapidly changing communities of crop pests in agroecosystems.